Threat to fish food safety in Nigeria: Role of antimicrobial usage and resistance in aquaculture - Lukman Adegoke Agbabiaka; Favour Ogechi Onwuzuruigbo; Olatunji Abubakar Jimoh (Aquaculture Reports)
Antimicrobial resistance (AMR) is a pressing global health concern exacerbated by the extensive use of antimicrobial compounds in aquaculture. This study aimed to assess antimicrobial usage (AMU) practices, knowledge of AMR, and its implications for fish food safety in the aquaculture sector. A cross-sectional study was conducted between January 2022 and December 2023, involving 120 fish farmers practicing either extensive or intensive management systems in Orlu Senatorial zone, Imo State, Nigeria. The study employed a multi-stage sampling method to select participants. Data were collected through structured questionnaires covering demographic characteristics, fish farm information, health management practices, AMU, and AMR knowledge. Findings revealed a male-dominated sector (90 %), with most fish farmers aged from 31 to 40 years (71.7 %) and married (81.7 %). Education levels were notably high, with 75 % having tertiary education. Fish farming was the primary occupation for all respondents. 93.33 % of the fish farmers reported disease outbreaks, primarily fungal infections (85 %). Despite widespread AMR awareness (66 %), only 57.5 % followed drug leaflet prescriptions, while 80 % administered drugs without disease outbreak. Tetracyclines were the most commonly used antibiotics (86.7 %), with 53.3 % not specifying target species. Practices aimed at preventing AMR were limited, with 33.3 % avoiding expired drugs. Notably, 86.7 % of farmers could not quantify antibiotic use. Concerningly, 50 % respondents used antibiotics for growth promotion, while 36.7 % used it prophylactically. This study revealed the need to invest in aquatic veterinary medicine and responsible antimicrobial use in aquaculture while strengthening regulatory frameworks for sustainable aquaculture. Implementing surveillance programs to monitor antimicrobial usage and resistance patterns in aquaculture settings is essential.